Dissecting nature and grotesque elements in Tunku Halim's Juriah's Song - Ahmad Jafni, Nur Fatin Syuhada; Wan Yahya, Wan Roselezam; Jujar Singh, Hardev Kaur (Universiti Putra Malaysia Press, 2016)
Tunku Halim's novella Juriah's Song (2008) revolves around the protagonist, Akri, and his encounter with the ghost of his late girlfriend, Juriah. Categorised as a horror genre, the characters and settings of this novella serve as important ground where elements of nature and the grotesque interweave to enhance the plot. In this paper, we examine the roles and functions of nature and the grotesque through a textual analysis of the chosen text by utilising the notion of 'the relationship between humans and nature' and the concept of the grotesque as proposed by Wolfgang Kayser, Sherwood and Phillip Thomson. Nature is depicted as a mirror that reflects the relationship between humans and nature. The grotesque, on the other hand, refers to various kinds of exaggerated emotions and distorted forms. Our findings demonstrate that both nature and the grotesque take on significant roles and affect the characters' perceptions, judgements and emotions, either positively or negatively. The generic designation of the grotesque applies to both actions and characters in the novel. Apart from functioning independently from each other, nature and the grotesque are also significant when they intertwine. When the two concepts are used together, nature acts as a catalyst to develop grotesque actions.